Evaluation of Temporomandibular Disorders after Orthognathic Surgeries: A Literature Review - Razmara, Farnoosh; Ghanadpour , Akram; Aleedawi, Zainab Abdulkareem; Khayamzadeh, Mina (Regeneration, Reconstruction & Restoration (Triple R), 2021)
Introduction: Maxillofacial orthognathic surgery is performed to repair or correct the skeletal anomalies of the jaw and its associated dental and facial structures. There is a conflict on whether orthognathic surgery has a negative or positive effect on temporomandibular disorders (TMD). The aim of this study is to review disorders of temporomandibular joint (TMJ) after orthognathic surgery. Materials and Methods: Data for this review was obtained from the articles published between 2010-2020 via PubMed, Google Scholar, Web of Sciences, and Scopus. The content keywords matched those used in PubMed and Mesh engines. Results: Based on the inclusion and exclusion criteria, 27 articles were included. Most of the selected articles were retrospective reviews and performed on class II and class III patients. Ages ranged from 19- 47 years. Pain reduction was reported in 11 studies, while 8 studies reported a click reduction post orthognathic operation. In two studies, decreased joint noises were reported after theorthognathic operation, and seven articles reported a decrease in maximum mouth opening. Three studies reported a bilateral sagittal split osteotomy (BSSO) and in one study, reduced and improved symptoms were reported after Le Fort I + (BSSO) surgery. One study exhibited that in retrognathic patients BSSO orthognathic surgery is less predictable in reducing TMD symptoms. Three articles showed that orthognathic patients with TMJ click have a high predictive value. Conclusion: To accomplish accurate results regarding TMD post orthognathic surgery, a larger number of subjects, as well as extended long term follow-up are required.